Failure Analysis of a Heat Exchanger 212-E9 - Dedi Wardianto; Karnova Yanel; Asmara Yanto (Jurnal Teknik Mesin, 2021)
Heat Exchanger 212-E9 is one part of the working fluid Debutanizer unit with seawater on inner tubes and H2S on the outside of the tubes. These tubes have failed in the form of leakage. Here the analysis of leakage and the remaining life of the tubes are based on data from the inspection and analysis of general corrosion of the tubes. Part inlet tube erosion-corrosion as well as there are some leaks in the tubes. From the results of inspections in the field, erosion-corrosion of the inlet tube caused by the flow of seawater on the inlet tube containing a solution/coarse material. While the leakage that occurs in tubes due to the H2S concentration is too high, which is equal to 2 mol % H2S. In fact, the recommended H2S concentration is 0.32 mol % H2S. The high level of concentration of H2S is not suitable with the level of material resistance tubes. In the analysis of remaining life obtained maximum corrosion rate in the tubes of 0.2372 mm/year. With the usage time now is 6 year obtained remaining life of 2.5 year again. Referring to the results of the analysis of leakage and remaining life on the tubes is recommended that a filtering of the seawater before entering into the tubes and provide tubes protector on the inlet tube so that tubes are protected from erosion-corrosion, and which is necessary to regulate the level of concentration of H2S Heat Exchanger flowing at the recommended standards.